Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

abx sq.+(b sq.-ac)x-bc =0

Asked by pulkithere1 17th February 2011, 9:52 AM
Answered by Expert
Answer:
Dear student,
 
abx2 + (b2 - ac)x - bc = 0
abx2 + b2x - acx - bc = 0
abx2 - acx + b2x - bc = 0
ax(bx - c) + b(bx - c) = 0
(ax + b) (bx - c) = 0
x = -b/a or x = c/b
We hope that clarifies your query.
Regards,
Team
TopperLearning
Answered by Expert 20th February 2011, 12:58 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!